Navigating Bias and Ensuring Fairness: Equity Unveiled in the AI-Powered Educational Landscape - Massala, Kélicia (Apprendre et enseigner aujourd’hui, 2023)
In an evolving world driven by technology, artificial intelligence (AI) is leading the way in bringing about changes. In the field of education, AI holds the potential to revolutionize learning by offering curricula data-driven insights and unparalleled access to knowledge. However, amid all the excitement surrounding these advancements, a significant concern arises : one that addresses the implications of AI presence in our educational landscape. This concern revolves around the possibility of biases within AI systems, which could undermine the promise of an inclusive education for everyone. The emergence of AI has sparked a growing awareness regarding biases that permeate aspects of our lives from social media feeds to hiring processes. However, the realm of education has largely remained unexplored in this regard until I decided to step forward. As an advocate, for fairness and equal opportunities, I decided to embark on a journey to uncover any biases embedded within the algorithms powering our virtual classrooms. Through an exploration of the influence of AI on education, let’s embark on a journey, towards uncovering the reality behind prejudice navigating territories, and ensuring that the educational landscape empowered by AI fosters inclusivity and fairness.